The correlation between students' curiosity and generic science skills in science learning - Herianto Herianto; Insih Wilujeng (Jurnal Inovasi Pendidikan IPA, 2020)
Curiosity is an attitude and action that seeks to know more deeply and broadly from something learned and acts as a driving force for learning. Generic science skills are thinking skills in intellectual abilities resulting from a combination of scientific knowledge and skills based on scientific knowledge. The purpose of this study was to determine the correlation between curiosity and students' generic science skills in science learning. This study uses a quantitative approach to explore the correlation between the variables studied. The total sample was 64 junior high school students, who were selected by random cluster sampling. Measurement of students' curiosity was carried out using a questionnaire, while generic science skills used multiple-choice test questions. The data obtained were then analyzed using simple linear regression on SPSS to determine the correlation between the two variables. The results showed that curiosity correlated with students' generic science skills (R = .389), with the category “low positive correlation.” The effect of curiosity on generic science skills is 15.1%, while other variables influence the rest.